Preparing of Controlled Release Systems for Atenolol and Studying it is in Vitro Dissolution and Swelling - misanjas, misanjas; R . Abdul - Azeez , Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
In this study, the appropriate polymer solutions were prepared to create chitosan/PVA blends. By altering the ratio of the ingredients, several chitosan/PVA mixtures were produced, as follows: 12% chitosan and 88% PVA, 40% chitosan and 60% PVA, and 15% chitosan and 85% PVA. To generate physically crosslinked hydrogels for the drug delivery of atenolol, several acid cross-linkers, such as fumaric acid and phthalic acid, were applied to the chitosan/PVA blends. The formulations included 15% chitosan and 85% PVA with 0.02% (0.0024, 0.0041, 0.02) mol of fumaric acid, as well as 15% chitosan and 85% PVA with 0.002, 0.003, and 0.0064 mol of phthalic acid. Using an ultraviolet-visible spectrophotometer, the chemical structures of the modified and unmodified chitosan (Chitosan/PVA) hydrogels were examined. Results regarding the formation of ionic cross-links between the protonated hydroxyl groups of the chitosan and the anionic functional groups of the cross-linking agent were established. The swelling ratio was determined for each hydrogel structure as a function of time in three distinct fluids with pH values of 2, 4, and 7.5, and at three distinct temperatures of 42°C and 44°C. The samples with the greatest swelling ratios were identified as PVA.PA0.002 (chitosan) and PVA.FA0.0024.